Water Microbial Contamination in Tikrit City - Aya Jameel Rasheed; Sarah Abdulhameed Hasan; Saba AbdulKareem Mustafa (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
In the world consequently, pollution of water has become a great concern, and with emphasis on the quality of water especially on those which originate from natural sources, with regard to water borne diseases and their causing pathogens. Some of the more familiar water borne pathogens include: aquatic or enteric bacteria such as Salmonella typhi, Shigella, Coliform bacteria; viruses; and Protozoa. Also relevant to diarrhea are rotavirus, astrovirus, adenovirus, norovirus, picobirnavirus, and enterovirus. This research work was done on a cross-sectional study basis over a period of four months, from April to October of the year 2022 at various water supply stations in Tikrit City, Salah Al-Deen province. Grab samples were taken from both the wells and the Tigris River to carry out microbiological processing and quality check in the laboratory. The samples used in this study included river and well water sources taken at the water treatment centers. Samples were collected at three points in the Tigris River and at three points from wells, although the points varied across the different sites. The findings were mainly secular for E. coli followed by P. aeruginosa and parasite such as Giardia cysts, and amoebic cysts.